2013
DOI: 10.1186/1471-230x-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of AFP, CEA, CA125 and CAl9-9 improves the sensitivity for the diagnosis of gastric cancer

Abstract: BackgroundThe detection of serum tumor marker becomes a common method for screening tumors. However, this method has not been widely used for routine gastric cancer screening. In this study we aimed to determine whether the combined use of tumor markers may increase the sensitivity for the diagnosis of gastric cancer.MethodsSerum AFP, CEA, CA125 and CA19-9 levels were measured in 149 patients with gastric cancer, 111 patients with benign gastric diseases and 124 healthy people, who visited the First Affiliated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 8 publications
8
90
2
Order By: Relevance
“…The results in the present study were similar to those previously obtained: In a systematic review (9) of 187 publications with data for CEA and CA19-9, and 19 publications with data for CEA, CA72-4 and CA19-9, the positive rates were 21.1% for CEA, 27.8% for CA19-9 and 30.0% for CA72-4. In a study of 149 Chinese patients with GC, He et al (10) demonstrated that the positive rates for CEA and CA19-9 were 17.4 and 20.8%, respectively, which were not significantly different. In a subsequent study of Chinese patients with GC, the preoperative serum positive rate of CEA was 24.0%, which was similar to the serum positive rate of CA19-9 (18.9%) (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results in the present study were similar to those previously obtained: In a systematic review (9) of 187 publications with data for CEA and CA19-9, and 19 publications with data for CEA, CA72-4 and CA19-9, the positive rates were 21.1% for CEA, 27.8% for CA19-9 and 30.0% for CA72-4. In a study of 149 Chinese patients with GC, He et al (10) demonstrated that the positive rates for CEA and CA19-9 were 17.4 and 20.8%, respectively, which were not significantly different. In a subsequent study of Chinese patients with GC, the preoperative serum positive rate of CEA was 24.0%, which was similar to the serum positive rate of CA19-9 (18.9%) (21).…”
Section: Discussionmentioning
confidence: 95%
“…However, the specificity and sensitivity of serum tumor markers considered in isolation are not satisfactory in GC, particularly in the early stage (9). Therefore, certain researchers have previously used combinations of markers, since they can improve the sensitivity for diagnosis of GC (10)(11)(12). Yang et al (13) demonstrated that the sensitivities of CA72-4, CEA, cancer antigen 125 (CA125) and CA19-9 for GC were 33.0, 25.5, 31.1 and 38.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2006;Ucar et al, 2008;He et al, 2013), 5.6-50% for CA 19-9 (Ychou et al, 2000;Hwang et al,2004;A.M. et al, 2006;Bagaria et al, 2013), 11.1-54.7% for CA 242 (A.M. et al, 2006Zhu et al, 2012;Li et al, 2013;Yu et al, 2013), and 24-41% for CA 50 (Kuusela et al, 1987;Nilsson et al, 1992;Mittal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As for possible explanations of the gap of CEA levels between GC tissues and the sera, there have been several reports that the amount of CEA released into the circulation does not depend mainly on the tissue CEA level, but depends on distribution patterns within the cancerous tissues, tumor differentiation and lymphovascular invasion [29][30][31] ducted immunohistochemical analysis and found that the appearance of CEA in the surrounding stroma led to the elevation of blood CEA levels due to the abnormal distribution of CEA on the basolateral plasma membrane of colorectal cancer cells [32]. Although previous studies demonstrated that CEA-producing GC and CA19-9-producing GC have different characteristics in morphology, histopathology and metastatic preference, the prognostic values of serum CEA and CA19-9 are still under debate [5,6,9,14].…”
Section: Discussionmentioning
confidence: 99%